Leflunomide inhibits transendothelial migration of peripheral blood mononuclear cells. Issue 12 (16th November 2004) - Grisar, J; Aringer, M; Köller, M D; Stummvoll, G H; Eselböck, D; Zwölfer, B; Steiner, C W; Zierhut, B; Wagner, L; Pietschmann, P; Smolen, J S
Abstract : Objectives: To test whether the active metabolite of leflunomide (LEF-M), in addition to blocking the proliferation of activated lymphocytes by inhibiting dihydro-orotate dehydrogenase (DHODH), influences the transendothelial migration (TEM) of peripheral blood mononuclear cells (PBMC). Methods: In an in vitro model of PBMC transmigration through an endothelial cell (EC) barrier, PBMC were re-collected in three groups: cells not adherent to the EC, cells bound to, and cells which had migrated through, the EC layer. Experiments in which cells were pretreated with LEF-M (in the absence or in the presence of uridine) were compared with parallel experiments in the presence of medium alone. Results: Preincubation of EC with LEF-M led to a 36 (SEM 16)% reduction in PBMC TEM (p<0.05). Likewise, preincubation of PBMC induced a reduction in their TEM of 39 (9)% (p<0.005). Incubation of both PBMC and EC with LEF-M had an additive effect (mean reduction of 48 (6)%, p<0.005). Incubation of PBMC with LEF-M also decreased monocytic CD44 expression (p<0.005) and PBMC-hyaluronan binding (p<0.05). Incubation of cells with LEF-M and uridine in addition to LEF-M reversed the inhibition of migration, suggesting that the observed effects were due to DHODH inhibition. Fluorocytometric analysis of PBMC subsets within the migrated population showed a decrease of monocytes, but not of B or T cells, after LEF-M treatment. Conclusions: LEF-M reduces monocytic adhesion molecule expression and TEM and may thus interfere with monocyte and EC activities in RA. Thus, the clinical effects of leflunomide may, at least in part, be due to blocking cell traffic into the inflamed synovia.